Nonlinear Dynamics, Volume 2 Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014 - Kerschen, Gaetan.; Kerschen, Gaetan. (Conference Proceedings of the Society for Experimental Mechanics Series,, 2014)
This critical collection examines a range of nonlinear dynamics, from nonlinear modal analysis to nonlinear systems to nonlinear modeling & simulation, as presented in early findings and case studies from the Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014. The collection includes papers in the following general technical research areas:  ·         Nonlinear Oscillations ·         Nonlinear Simulation Using Harmonic Balance ·         Nonlinear Modal Analysis ·         Nonlinear System Identification ·         Nonlinear Modeling & Simulation ·         Nonlinearity in Practice ·         Nonlinear Systems ·         Round Robin on Nonlinear System Identification.